Statistical Study on the Increase in Begging Among Children under the Age of 18 - Salman, Ibrahim Abdulhussein Saleh; Sahin, Alaa Khairy Alwan; Shehab, Tabarak Rafid Sami; Jassim, Janan Mohammed Abd; Katea, Zaid Kazim Zaij (American Journal of Biomedicine and Pharmacy, 2024)
Through the research, we reached several conclusions, including: - From Table No. (1) the calculated value reached (0.000) which is less than the significance level (0.05) and thus we reject the null hypothesis and accept the alternative hypothesis From Table No. (2) the calculated value reached (0.040) which is less than the significance level (0.05) and thus we reject the null hypothesis and accept the alternative hypothesis From Table No. (3) the calculated value reached (0.037) which is less than the significance level (0.05) and thus we reject the null hypothesis and accept the alternative hypothesis From Table No. (4) the calculated value reached (0.029) which is less than the significance level (0.05) and thus we reject the null hypothesis and accept the alternative hypothesis From Table No. (5) the calculated value reached (0.036) which is less than the significance level (0.05) and thus we reject the null hypothesis and accept the alternative hypothesis From Table No. (6) the calculated value has reached (0.019) which is less than the significance level (0.05) and thus we reject the null hypothesis and accept the alternative hypothesis From Table No. (7) the calculated value has reached (0.000) which is less than the significance level (0.05) and thus we reject the null hypothesis and accept the alternative hypothesis From Table No. (8) the calculated value has reached (0.000) which is less than the significance level (0.05) and thus we reject the null hypothesis and accept the alternative hypothesis From Table No. (9) the calculated value has reached (0.040) which is less than the significance level (0.05) and thus we reject the null hypothesis and accept the alternative hypothesis Alternative From Table No. (10) the calculated value reached (0.025) which is less than the significance level (0.05) and therefore we reject the null hypothesis and accept the alternative hypothesis From Table No. (11) the calculated value reached (0.025) which is less than the significance level (0.05) and therefore we reject the null hypothesis and accept the alternative hypothesis From Table No. (12) the calculated value reached (0.037) which is less than the significance level (0.05) and therefore we reject the null hypothesis and accept the alternative hypothesis From Table No. (13) the calculated value reached (0.251) which is greater than the significance level (0.05) and therefore we reject the alternative hypothesis and accept the null hypothesis From Table No. (14) the calculated value reached (0.773) which is greater than the significance level (0.05) Therefore, we reject the alternative hypothesis and accept the null hypothesis. From Table No. (15), the calculated value reached (0.831), which is greater than the significance level (0.05). Therefore, we reject the alternative hypothesis and accept the null hypothesis.